Behavioral Neurobiology of Stress-related Disorders - Pariante, Carmine M.; Lapiz-Bluhm, M. Danet (Springer eBooks, 2014)
Stress is such an over-used word that it is at time difficult to define its core features. When is an environment stressful? What does a stressful environment do to the brain and to the body? What are the biological mechanisms by which a stressor affects us? How does stress contributes to the onset and the progression of mental disorders? How do the effects of stress change over the life-time of an individual? These are just some of the overarching questions addressed by this book, thanks to the contribution of some of the world leading experts on the neurobiology of stress at the pre-clinical and clinical levels. Topics include current advances on the neurobiology of stress on various neurobiological systems such as immune, hypothalamic-pituitary-adrenal (HPA) axis, neurogenesis and neuroplasticity, neurotransmitter (glutamate, noradrenaline, dopamine, serotonin and endocannabinoid), neuropeptides, cognition and emotional processing as well as in utero and early postnatal effects. The clinical chapters deal with the relationship of stress and mental disorders such as depression, posttraumatic stress disorder (PTSD), anxiety disorders, schizophrenia, bipolar disorder, substance abuse and addiction, dementia and age-related cognitive decline as well as resilience to stress. Thus, this book brings together some of the most updated and authoritative views on the effects of stress of brain and behavior.